Electron-Impact Ionization of SiCl, $SiC_2$ and $SiCl_4$ Molecules (Journal of Atomic and Molecular Sciences, 2013)
Total ionization collision cross sections are calculated for silicon chloride compounds namely $SiCl,$ $SiCl_2$ and $SiCl_4$ applying binary-encounter-Bethe (BEB) and modified BEB model for projectile energy from the ionization threshold to 1000 eV. The total ionization cross sections obtained using the binary-encounter-Bethe (BEB) model and the modified BEB model are compared with experimental and theoretical results. This model has been found to be successful for a wide range of molecules but for silicon chloride molecules the results are not in good agreement with experimental data.